Mathematical Model of Energy Transformation Processes in Barrel System for Determining Shooting Performance - Oleksandr Brunetkin; Vitalii Kuzmenko; Olha Soloviova (Energy Engineering and Control Systems, 2022)
A phenomenon has been singled out that is present during almost every shot. It manifests itself in a muzzle blast in the form of soot of a certain amount. The Bell-Boudoir thermochemical reaction has been defined, which explains the formation of soot in powder gases during the shot. The conditions making it possible to manifest have been mentioned. A method for solving the problem of internal ballistics has been developed, enabling to determine the temperature of powder gases along the length of the gun barrel at different times and at different positions of the projectile in the barrel. The modelling of the powder gases temperature distribution in the barrel space between the charging chamber and the moving projectile has been carried out in the model system. The possibility of changing the length of the zone of the Bell-Boudoir reaction (the zone of soot formation) depending on the initial data has been shown. The use of a fresh powder charge and a degraded one has been modelled.